Juvenile myoclonic epilepsy : characterisation of the syndrome and examination of linkage to the HLA locus in families from the Western Cape - Carr, Jonathan Ambrose (Department of Medicine, 2020)
The primary purpose of this study was the identification of patients with JME, in order to identify suitable families for studying the nature of the linkage of the syndrome of JME to the HLA (Human Leukocyte Antigen) locus. This search for suitable candidate families necessitated examination of a large number of individuals with a range of IGE syndromes, and patients were classified into these various syndromes. Patients with JME were thereafter investigated further. The study could thus be broken up into three sections: i) Determination of the various syndromes of IGE. ii) Characterisation of JME. iii) Linkage Studies on JME patients.